Transformasi Pembelajaran Digital melalui Implementasi Google Classroom dalam Penguatan E-Learning Pada Mahasiswa - Afrillia, Imelda (Universitas Pahlawan Tuanku Tambusai, 2025)
Developments in educational technology are encouraging higher education institutions to optimize digital learning models, including the use of Learning Management Systems (LMS). E-learning implementation has not been optimal due to low digital literacy among instructors and inconsistent variations in learning platforms. This study aims to describe the process of digital learning transformation through the implementation of Google Classroom. The research method used a qualitative descriptive approach through five main stages: coordination, Google Classroom LMS design, socialization, implementation, and evaluation. Data were collected through digital literacy pre-tests, observations of learning activities, and student satisfaction surveys. The results indicate that Google Classroom improves learning effectiveness through ease of access, material integration, discussion forums, and assignment management. The evaluation demonstrated increased student understanding, higher engagement, and a positive response to the flexibility of online learning. This implementation demonstrates that Google Classroom can be a strategic tool in supporting digital learning transformation in Indonesia.